A note on electrometer intercomparison: a routine quality assurance check - Gloi, Aime M.; Kibisu, Patrice L. (International Journal of Research in Medical Sciences, 2024)
Background: This study evaluates the accuracy of the Max-4000 and Model 206 electrometers in measuring ionization readings during radiation therapy dosimetry. The goal is to assess their performance and reliability to determine if they can provide interchangeable and reliable measurements. These comparisons are crucial to ensure accurate radiation dose delivery to patients, improving treatment outcomes and patient safety in clinical settings. Methods: Measurements were conducted using a Varian TrueBeam Edge at different photon energies (6 MV, 6 FFF, 10 MV, and 10 FFF) and field sizes ranging from 3.0 to 30.0 cm. The setup included a solid water phantom with an ionization chamber positioned at 5 cm depth and a 95 cm source-to-surface distance. Both electrometers, ADCL calibrated, were compared for accuracy and precision using the Bland-Altman method, regression analysis, and correlation analysis. Results: The stability of individual charge readings was within ±0.005% for all energies, field sizes, and electrometers. The Bland-Altman analysis showed a bias of -0.0282 [0.0158 to -0.0405, 95% confidence interval (CI)] with a correlation coefficient (R²) of 0.999 (p<0.001) for 6 MV, -0.0345 [0.0283 to -0.0408, 95% CI] with an R² of 0.999 (p<0.001) for 6 FFF, -0.0373 [0.0305 to -0.0441, 95% CI] with an R² of 0.999 (p<0.001) for 10 MV, and -0.00454 [0.00360 to -0.0127, 95% CI] with an R² of 0.999 (p<0.001) for 10 FFF. Conclusions: this study establishes a framework for comparing two ADCL electrometers using Bland-Altman analysis, linear regression, and mean absolute percentage error (MAPE).